In Silico Analysis of Hepatitis B Virus Genotype D Subgenotype D1 Circulating in Pakistan, China, and India. (July 2019) - Bahar, Muneeb; Pervez, Muhammad Tariq; Ali, Akhtar; Babar, Masroor Ellahi
The focus of this study was the computational analysis of hepatitis B virus (HBV) genotype D subgenotype D1 in Pakistan, China, and India. In total, 54 complete genome sequences of HBV genotype D subgenotype D1 were downloaded from National Center for Biotechnology Information (NCBI). Of these, 6 complete genome sequences were from Pakistan, 14 were from China, and 34 were from India. Sequence alignment showed less than 4% divergence in these sequences. C and X genes showed divergence of less than 3%. Comparison over the S gene showed more than 97% similarity among the nucleotide sequences of genotype D subgenotype D1. The identity and similarity matrix of 54 nucleotide sequences of HBV genotype D subgenotype D1 from Pakistan, China, and India revealed more than 93% identity and 93% similarity. Phylogenetic analysis highlighted that complete genome isolates of HBV circulating in Pakistan had the closest evolutionary relationship with its neighboring countries China and India. China's (HQ833466) and Pakistan's (AB583680.1) isolates shared the same ancestor. Gene structure analysis showed that "P" gene exons were the longest, about three-fourth of the genome size, whereas gene "S" had the second longest coding regions with 2 exons and 1 intron. However, "C" and "X" genes had 1 smallest exon. X proteins had proven role in spreading of the HBV infection diseases. For HBx analysis, 1 X protein sequence of HBV genotype D subgenotype D1 belonging to each country was obtained. Homology models of the 3 X proteins generated using SWISS-MODEL revealed GMQE (Global Model Quality Estimation) = 0.1. Global and local quality estimate scores including Z -scores for Qualitative Model Energy Analysis (QMEAN) C-beta, all-atom, solvation, and torsion energy scores were similar indicating good quality, accuracy, and reliability of the predicted models. Three-dimensional (3D) visualization showed similar structures and Ramachandran plots showed a high percentage of protein residues into the favorable region for X protein models.